Autonomic correlates at rest and during evoked attention in children with attention-deficit/hyperactivity disorder and effects of sympathomimetic medication - Viljoen, Margaretha (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.